Zarządzanie zasobami ludzkimi w organizacjach pozarządowych – wybrane problemy - Marcin Grobelak (Edukacja Ustawiczna Dorosłych, 2022)
The article presents issues related to personnel management in non-governmental organizations. It would be difficult to list all the problems that representatives of social organizations face on a daily basis. The aim of the publication is to describe selected problems in the area of personnel management in NGOs and to present recommendations for leaders of non-governmental organizations in relation to the problems of professional burnout, overtime and low wages. Preventive measures as well as the solutions proposed in the article will allow to strengthen the human resources of the organization and thus affect the effectiveness of units representing the third sector.